Assisting consumers in self-medication: reflections on the role of support staff in community pharmacy - Veiga, Paulo (2015)
Poster presented at the 43rd ESCP Symposium on Clinical Pharmacy – Patient Safety : Bridging the Gaps. Copenhagen, 22nd-24th October 2014.